Artificial intelligence in civil engineering: emerging applications and opportunities - Nyokum, Taba; Tamut, Yamem (Frontiers in Built Environment, 2025)
Artificial intelligence (AI) is rapidly transforming civil engineering by harnessing vast data streams and advanced computational methods. This review provides a comprehensive survey of AI innovations in civil engineering, covering key technologies (machine learning, deep learning, natural language processing, computer vision, robotics, and generative AI) and their applications across design, construction, monitoring, transportation, geotechnical, environmental, and asset management domains. This paper discuss how AI-driven models and systems improve efficiency, safety, and sustainability, while also addressing challenges such as data limitations, model interpretability, and ethical concerns. Emerging trends—such as digital twins, smart cities, and quantum computing—are highlighted, along with the growing need for workforce skills in AI. By synthesizing recent studies, this article aims to clarify how AI is reshaping civil engineering practice and to identify opportunities and gaps for future research.